2018
DOI: 10.3390/ijms19123993
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-Inducible Protein DRR1 Exerts Distinct Effects on Actin Dynamics

Abstract: Cytoskeletal dynamics are pivotal to memory, learning, and stress physiology, and thus psychiatric diseases. Downregulated in renal cell carcinoma 1 (DRR1) protein was characterized as the link between stress, actin dynamics, neuronal function, and cognition. To elucidate the underlying molecular mechanisms, we undertook a domain analysis of DRR1 and probed the effects on actin binding, polymerization, and bundling, as well as on actin-dependent cellular processes. Methods: DRR1 domains were cloned and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 95 publications
1
4
0
Order By: Relevance
“…Several other cytoskeletal proteins like Arpc4, Vim, Tubb5, Klkb1, and Msn were also shown to be induced one week after HNK administration. These findings are in line with recent reports indicating the relevance of cytoskeletal dynamics in translating stressful environmental experiences into persistent changes of molecular and cellular function (38, 39). The fact that we identified a considerable number of cytoskeletal proteins to be specifically regulated by HNK (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Several other cytoskeletal proteins like Arpc4, Vim, Tubb5, Klkb1, and Msn were also shown to be induced one week after HNK administration. These findings are in line with recent reports indicating the relevance of cytoskeletal dynamics in translating stressful environmental experiences into persistent changes of molecular and cellular function (38, 39). The fact that we identified a considerable number of cytoskeletal proteins to be specifically regulated by HNK (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Fam107a is involved in neurite growth, neurodevelopment, and synaptic plasticity (Wang et al, 2019). The Fam107a gene can alter actin dynamics and cognition (Kretzschmar et al, 2018). Our results suggested that various genes involved in cilia formation, synaptic plasticity, and neuronal excitability were altered in 5‐HT6R −/− mouse tissues.…”
Section: Resultsmentioning
confidence: 99%
“…We observed an abnormal aggregation of spines, which might lead to increased dendritic width. In RNAseq, the Fam107a gene was found to be downregulated, which can alter actin dynamics and impact cognition (Kretzschmar et al, 2018). This finding is consistent with our results above.…”
Section: Discussionmentioning
confidence: 99%
“…In lung tissue homogenates, RTD-1 increased expression of BC055107 ( FAM107a , DDR1 ) by 2.497-fold. This stress-inducible actin-binding protein facilitates regulation of filamentous actin dynamics [ 32 ]. We also found a 2.562-fold increase in NPR3 .…”
Section: Resultsmentioning
confidence: 99%